Disparities in breast cancer mortality trends between 30 European countries: retrospective trend analysis of WHO mortality database. (11th August 2010) - Autier, Philippe; Boniol, Mathieu; LaVecchia, Carlo; Vatten, Lars; Gavin, Anna; Héry, Clarisse; Heanue, Mary
Abstract : Objective To examine changes in temporal trends in breast cancer mortality in women living in 30 European countries. Design Retrospective trend analysis. Data source WHO mortality database on causes of deaths Subjects reviewed Female deaths from breast cancer from 1989 to 2006 Main outcome measures Changes in breast cancer mortality for all women and by age group (<50, 50-69, and ≥70 years) calculated from linear regressions of log transformed, age adjusted death rates. Joinpoint analysis was used to identify the year when trends in all age mortality began to change. Results From 1989 to 2006, there was a median reduction in breast cancer mortality of 19%, ranging from a 45% reduction in Iceland to a 17% increase in Romania. Breast cancer mortality decreased by ≥20% in 15 countries, and the reduction tended to be greater in countries with higher mortality in 1987-9. England and Wales, Northern Ireland, and Scotland had the second, third, and fourth largest decreases of 35%, 29%, and 30%, respectively. In France, Finland, and Sweden, mortality decreased by 11%, 12%, and 16%, respectively. In central European countries mortality did not decline or even increased during the period. Downward mortality trends usually started between 1988 and 1996, and the persistent reduction from 1999 to 2006 indicates that these trends may continue. The median changes in the age groups were −37% (range −76% to −14%) in women aged <50, −21% (−40% to 14%) in 50-69 year olds, and −2% (−42% to 80%) in ≥70 year olds. Conclusions Changes in breast cancer mortality after 1988 varied widely between European countries, and the UK is among the countries with the largest reductions. Women aged <50 years showed the greatest reductions in mortality, also in countries where screening at that age is uncommon. The increasing mortality in some central European countries reflects avoidable mortality.